Effect of player substitutions on the intensity of second-half soccer match play - Danusa Dias Soares; João Carlos Bouzas; Luciano Sales Prado; João Batista Ferreira-Júnior; Rodrigo Figueiredo Morandi; Leonardo Gomes Coelho; Daniel Barbosa Coelho; Emerson Silami-Garcia (Universidade Federal de Santa Catarina, 2012)
Most soccer matches are conducted by coaches who usually make all player substitutions allowed. Therefore, it is extremely important to study these substitutions and their effects on the intensity of effort required from players. To date, no published studies have reported on this topic using heart rate (HR) as an intensity parameter. The objective of this study was to compare effort intensity (EI) of soccer players in the following situations: 1) first half (FH-EI); 2) second half (SH-EI); 3) second half with substitutions(SHS-EI). Forty-five male soccer players (18.5±1.2 years old, 74.25±5.79 kg, 182.6±8.55 cm, 9.56±2.47% body fat, 56.3±4.3 mLO2/kg/min) were evaluated during 29 official games. EI was considered as the mean HR, expressed as the percentage of each player's maximal HR (%HRmax) and as the time spent in each intensity zone (Z) according to %HRmax (Z1<70%; Z2 70-85%; Z3 85-90%; Z4 90-95%; Z5 95-100%). FH-EI (86.3±3.3%HRmax) was higher than SH-EI (80.6±4.4%HRmax) and SHS-EI (83.6±2.8%HRmax). SHS-EI was higher than SH-EI (p<0.05). Time spent in high-intensity zones was lower in SH-EI than in FH-EI, buthigher in SHS-EI when compared to SH-EI (p<0.05). It was concluded that the decrease in EI in the second half of soccer matches was attenuated by substitutions made at halftime, as evidenced by a longer time spent in high-intensity zones when compared to SH-EI.